Phenomenological Study of Smoking Behavior in Adolescents at State Sekolah Menengah Kejuruan (SMK) 1 Samarinda - Alvina, Octavia; Hendriani, Dwi; Tonapa, Emelia (STIKes Medistra Indonesia, 2025)
The current health problems were the high prevalence of smoking. The decision to smoke in teenagers began with the desire to try, while smoking behavior was due to not having enough knowledge about the dangers of smoking. This research aimed to determine the phenomenological picture, namely the factors that influence smoking behavior in teenagers at SMK Negeri 1 Samarinda. This type of research was qualitative with a phenomenological design. The research was conducted through in-depth interviews and observations. The research sample consisted of 7 informants at SMK 1 Samarinda who were determined using the purposive sampling technique have been. In predisposing factors, school teenagers have low knowledge and attitudes about smoking, which leads to smoking behavior. In enabling factors, school teenagers received pocket money that was used to buy cigarettes and the beginning of smoking when they were in junior high school, they were introduced directly by peers and assumed that cigarette advertisements did not influence school teenagers to smoke. In reinforcing factors, the closest people (family and teachers) knew and reprimand school teenagers when they smoke, while peers ignored the behavior. There were predisposing, enabling factors and reinforcing factors that influenced smoking behavior in teenagers. It was expected that teachers and parents improve regulations and facilities related to smoking in the school environment and provided support for teenagers to stop smoking. Teenagers are expected to be able to participate in all health program activities with an effort to reduce smoking habits.